Orthodontic Treatment of Patients with Mental and Intellectual Disabilities: A Systematic Review - Mehmani, Ilham Gasanaga; Mehmani, Vusala Rasim; Aliyev, Mammad Suad Afrail (Actual Dentistry, 2026)
Abstract. Patients with mental and intellectual disabilities exhibit higher levels of anxiety when anticipating orthodontic treatment compared to the general population. Despite this, the literature lacks systematic reviews addressing behavioral modification methods and the specific features of orthodontic therapy for this patient group. The aim of this review was to identify the main orthodontic problems and barriers in treating individuals with mental disorders, with a focus on developing recommendations to optimize orthodontic care. Materials and Methods. A literature review was conducted, including studies that examined behavior modification strategies and/or physical restraint methods used in the orthodontic treatment of patients with intellectual disabilities. The search was performed using the PubMed, Scopus, Embase, Cochrane Oral Health Group, and Dentistry & Oral Sciences Source databases for the period from 2002 to 2022. English-language articles meeting the inclusion criteria were selected, and the quality of the included studies was assessed using the Joanna Briggs Institute critical appraisal tools. Results. The review showed that most studies were descriptive and included individual clinical cases, while systematic studies and randomized controlled trials were largely absent. The main challenges in treatment included low patient motivation, difficulty maintaining oral hygiene, the need to adapt behavior management techniques, and the use of pharmacological or physical methods to ensure effective and safe treatment. Conclusions. The success of orthodontic therapy in patients with mental disorders depends on a combination of appropriate mechanotherapy, behavior modification techniques, and a multidisciplinary approach. Important factors include patient motivation and the cooperation of parents or caregivers. Further systematic studies are required to develop clear guidelines for providing orthodontic care to individuals with mental and intellectual disabilities.